Contribution of diverse monsoon precipitation over Central and Northern India during mid to Late Holocene. (25th February 2019) - Kumar, P.; Sanwal, J.; Dimri, A.P.; Ramesh, R.
Abstracts: The Indian summer monsoon (ISM) precipitation pattern over Indian subcontinent is looked through various high resolution speleothem oxygen (δ 18 O) isotope records from Mid to Late Holocene. The six cave locations distributed from central to northern India describing regional climatic conditions due to stalagmite deposition are considered. The stalagmite deposition reflects precipitation patterns by temporal variations of δ 18 O values. Oxygen isotope values reflect cumulative precipitation that is basically interpreted by averaged latitudinal site of inter tropical convergence zone (ITCZ). Under the Paleoclimate Modelling Intercomparison Project Phase III (PMIP3) simulation, Commonwealth Scientific and Industrial Research Organisation Mk3L version 1.0 – Part 2 (CSIRO-Mk3L-1-2) model output shows ITCZ movement from Bay of Bengal (BoB) to Arabian Sea (AS) during Mid to Late Holocene which resulted due to solar insolation changes. It reflects precipitation shift from BoB to AS as well as to core monsoon zone (CMZ) to the western Himalayas. The past millennium epoch, which consists little ice age (LIA) and middle warm period (MWP), shows large variations in 850 hPa geopotential height leading to high anomalous precipitation variability all over India during ISM. The high fluctuation in δ 18 O values during Mid Holocene over northern India led to drought conditions due to which Indus valley civilization vanished. The present study shows that the Himalayas received higher precipitation during late Holocene. That is basically governed by western disturbances (WD) as well as ISM. Present study summarizes that the mean annual precipitation cycle for entire epoch was roughly similar, but spatial distribution of precipitation during various epoch was quite divergent from Mid to Late Holocene. The onset of ISM was also similar but, withdrawal was comparatively unalike. Wherever, peaks of seasonal precipitation were alike over Indian subcontinent region, spatial distribution of precipitation were unlike.